Postharvest Losses, Current Issues and Demand for Postharvest Technologies for Loss Management in the Main Banana Supply Chains in Sri Lanka - Wasala, W M C B; Dissanayake, C A K; Dharmasena, D A N; Gunawardane, C R; Dissanayake, T M R (Journal of Postharvest Technology, 2014)
Banana is the main fruit crop cultivated in Sri Lanka. It’s a commercial crop giving high income to the cultivators. It is distributed from farm gate to consumers through the supply chain which involves farmer, collector, whole seller, retailer and transporter and with a high post harvest loss. Therefore, this study was conducted to assess the present status of the banana supply chain. A total sample of 100 including farmers, collectors, whole sellers, transporters and retailers were randomly selected from two growing areas and a high banana retailing municipal council areas. Data were gathered through a survey using a questionnaire, key informant interviews, direct observations and secondary sources. The study revealed that the banana supply chain follows the conventional chain with some deviations. All whole sellers were acting as bulk transporters. Majority of stakeholders preferred and transported bananas as whole bunches bulk packed in vehicles. Preference in selling in retail outlets were also as intact bunches. The commonly used transportation vehicles were two wheel tractors, open trucks, and lorries. The total postharvest loss of banana was 20 % from farm gate to retailer. A suitable bulk packing method should be introduced to reduce the post harvest loss of banana.